Ultimate performance : measuring human resources at work - Burkholder, Nicholas C. (Hoboken, N.J. : John Wiley & Sons, 2007)
Meeting the challenges of high-performance HR. Until 1760 ships routinely disappeared, ran aground, or sank because seafarers could not measure longitude. The cost in life and property was immense. Today, business faces a similar challenge, as the failure to measure human resources performance is just as costly and deadly to modern organizations.
Imperatives of metrics -- A path to alignment -- Supporting human capital decision making -- Employee assets and contribution -- Employee contribution to risk -- The employee lifecycle--a metrics roadmap from the C-level -- Missions, objectives, and metrics -- Measuring staffing--a better approach to hiring metrics -- Beyond hiring--metrics for employee development and retention -- Succession planning and internal mobility -- Current measurement practices--lessons from the field -- Case studies--metrics in action -- Human capital and organizational performance -- HR outsourcing and metrics -- A practical guide to building your ultimate dashboard -- Conclusion.
Includes bibliographical references (pages 259-262) and index.
Print version record.
John Wiley and Sons
Keywords: Performance -- Measurement; Organizational effectiveness -- Measurement; Employees -- Rating of; Performance standards; Strategic planning -- Evaluation; x; Rendement au travail -- Normes; x; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Employees -- Rating of; Organizational effectiveness -- Measurement; Performance -- Measurement; Performance standards; Strategic planning -- Evaluation; Personeelsmanagement; Werknemers; Personeelsbeoordeling; Human Capital; Vaardigheden